Potential candidate maternal serum miRNAs for the diagnosis of fetal congenital heart disease: miRNA candidates for diagnosis of fetal CHD - Xi, Yimeng; Lu, Enkang; Ruan, Xinyan; Wu, Ruoyun; Wu, Lijun; Zhou, Ting; Gu, Haitao; Wu, Yun (Cellular and Molecular Biology, 2024)
Congenital heart disease (CHD) is one of the most significant birth defects leading to infant mortality worldwide. Circulating microRNAs (miRNAs) are emerging as novel biomarkers for the detection of cardiovascular diseases. In this study, we aimed to investigate the role of maternal serum miRNAs expression as biomarkers in the diagnosis and prediction of children with CHD. High-throughput sequencing of peripheral blood from pregnant women with abnormal and normal fetal hearts identified 1939 differentially expressed miRNAs, the first 11 of which were selected as predictive biomarkers of CHD. The expression of miRNAs in more clinical samples was then quantitatively verified by reverse transcriptase polymerase chain reaction and the correlation between abnormal miRNAs and CHD was analyzed. Two miRNAs (hsa-miR-3195 and hsa-miR-122-5p) were found to be significantly down-regulated in pregnant women with fetal CHD. By further bioinformatics analysis, we predicted that hsa-miR-3195 and hsa-miR-122-5p could induce CHD by influencing biometabolic processes. hsa-miR-3195 and hsa-miR-122-5p may serve as novel non-invasive biomarkers for prenatal detection of fetal CHD.